The Influence of Self Efficacy on Adversity Quotient in Students at SMP X Sidoarjo: Pengaruh Self Efficacy terhadap Adversity Quotient pada Siswa di SMP X Sidoarjo - Muhammad Novran Rachmadani; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Adversity quotient represents students’ capacity to confront academic challenges and persist in learning tasks. Specific Background: In junior high schools, variations in students’ adversity quotient are closely associated with psychological factors, particularly self efficacy. Knowledge Gap: Previous studies predominantly focused on senior high school populations, leaving limited evidence regarding junior high school contexts. Aims: This study aimed to examine the relationship between self efficacy and adversity quotient among students at SMP X Sidoarjo using a quantitative correlational approach. Results: Data from 131 students revealed that most participants were in the moderate category for both self efficacy (72%) and adversity quotient (70%). Simple linear regression indicated a significant positive relationship (β = 0.378; p < 0.05), with self efficacy accounting for 51.3% of the variance in adversity quotient. Novelty: This research provides empirical evidence from a junior high school setting supported by preliminary field observations, extending existing findings predominantly derived from SMA/SMK populations. Implications: The findings highlight the importance of strengthening students’ self efficacy through counseling services, guidance programs, and supportive learning environments to foster higher adversity quotient and academic resilience. Keywords: Self Efficacy, Adversity Quotient, Junior High Students, Educational Psychology, Learning Resilience Key Findings Highlights: Most students demonstrated moderate psychological readiness in facing academic difficulties. Regression analysis confirmed a strong positive statistical association between personal confidence and resilience. Self-belief explained over half of students’ persistence capacity, with remaining variance linked to external factors.